2011
DOI: 10.1073/pnas.1012594108
|View full text |Cite
|
Sign up to set email alerts
|

Stable folding core in the folding transition state of an α-helical integral membrane protein

Abstract: Defining the structural features of a transition state is important in understanding a folding reaction. Here, we use Φ-value and double mutant analyses to probe the folding transition state of the membrane protein bacteriorhodopsin. We focus on the final C-terminal helix, helix G, of this seven transmembrane helical protein. Φ-values could be derived for 12 amino acid residues in helix G, most of which have low or intermediate values, suggesting that native structure is disrupted at these amino acid positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 49 publications
1
47
2
Order By: Relevance
“…Insertion of the second, C domain of LacY does not appear to require the equivalent regions of the domain at the initial helix of the C domain to have enhanced stability. This is despite the fact 13 that that the C domain can be expressed and folded in the absence of the N domain 32 , and that the two domains exhibit pseudo symmetry and are thought to arise from gene duplication 33 .…”
Section: Relative Stability Of Helix I and Viimentioning
confidence: 99%
“…Insertion of the second, C domain of LacY does not appear to require the equivalent regions of the domain at the initial helix of the C domain to have enhanced stability. This is despite the fact 13 that that the C domain can be expressed and folded in the absence of the N domain 32 , and that the two domains exhibit pseudo symmetry and are thought to arise from gene duplication 33 .…”
Section: Relative Stability Of Helix I and Viimentioning
confidence: 99%
“…ϕ-Value analysis of the seven-transmembrane helix (TM) protein bacteriorhodopsin has now been performed twice. The initial analysis highlighted a TS with D-level compaction (17) wherein helix B (near the N terminus) has native-like contacts in the TS and thus constitutes part of the folding nucleus (18), whereas helix G (close to the C terminus) is essentially unfolded (19). It was subsequently found that bulk solution concentration of detergent can alter the folding kinetics of bacteriorhodopsin (20).…”
mentioning
confidence: 99%
“…The protein solubilized by 0.4 M L-arginine and 2 M urea was refolded through stepwise dialysis and resulted in a recovery over 50% soluble protein, which was 30% higher than that of the protein solubilized without L-arginine. The more hydrophobic microenvironment of the protein solubilized with L-arginine may reduce the susceptibility to aggregation, and thus improving the protein folding [29,30].…”
Section: Discussionmentioning
confidence: 99%